Crescimento e saúde de jundiás (Rhamdia quelen) criados em sistema de bioflocos – BFT - Battisti, Eduardo Kelm (2020)
Biofloc system (BFT) is a super-intensive production system, characterized by the action of microorganisms in the water, in order to improve the assimilation of nitrogen compounds that may serve as a supplementary food source. The aim of this study was to evaluate the use of BFT for the specie (Rhamdia quelen), the influence of the system on the development and health of post-larvae and juvenile silver catfish. Three experiments were carried out, one lasting 21, 45 and 70 days. In experiment I, the post-larvae received mash feed with 45% crude protein (CP), were stocked in different densities (10, 20, 30 and 40 larvae per liter). In experiment II, juveniles of silver catfish received 36% CP commercial feed, also stored in different densities (10, 20 and 30 grams per liter). In experiment III the experimental design was 2x2 factorial, one factor was feeding strategy (feeding 5 days a week and 7 days a week) the other factor was CP of the offered ration, the fish received commercial feed of 32 and 36% CP. Throughout experiment I (at 7, 14, 21 and 28 days) biometrics were performed as well as at the end of experiments II and III, in (II and III) growth parameters were evaluated, blood, liver, kidney and muscle samples were collected for health assessment of the fish. The results of the three experiments show that BFT can be used for silver catfish. In experiment I, the results indicated that post-larval growth was not affected in the BFT system until 40 post-larvae / L, but there was higher survival in the density of 20 post-larvae / L. In experiment II, the higher density of 30 grams / liter resulted in better growth for juveniles of silver catfish. In experiment III, based on the results found, it is possible to feed juveniles of silver catfish fewer days of the week and with fewer protein, without impairing the fish growth in the BFT. It is possible to use the BFT system for larviculture and growth of silver catfish, this system may contribute to the fish production chain of native species in a sustainable way.